2019
DOI: 10.1111/gcb.14734
|View full text |Cite
|
Sign up to set email alerts
|

Microbial community responses reduce soil carbon loss in Tibetan alpine grasslands under short‐term warming

Abstract: Changes in labile carbon (LC) pools and microbial communities are the primary factors controlling soil heterotrophic respiration (R h ) in warming experiments. Warming is expected to initially increase R h but studies show this increase may not be continuous or sustained. Specifically, LC and soil microbiome have been shown to contribute to the effect of extended warming on R h . However, their relative contribution is unclear and this gap in knowledge causes considerable uncertainty in the prediction of carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…Previous studies showed that warming could stimulate microbial respiration due to increased microbial biomass C (Liu et al., 2019), soil nutrient availability (Ali et al., 2018), root exudates (Li et al., 2013), enzymatic activity (Bragazza et al., 2012; Li et al., 2017), or plant production (Euskirchen et al., 2009). Some other studies showed opposite results; that is, microbial respiration inhibited by warming, which resulted from decreased soil water availability (Fang et al., 2018; Liu et al., 2009), labile C (Li et al., 2019), microbial biomass C (Chen, et al., 2016), or enzymatic activity (Garcia‐Palacios et al., 2018). As a result, these contrasting responses of microbial metabolic rate to warming led to large uncertainties and contradictory predictions of climate‐C feedbacks (Bradford et al., 2010; Hartley et al., 2007, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed that warming could stimulate microbial respiration due to increased microbial biomass C (Liu et al., 2019), soil nutrient availability (Ali et al., 2018), root exudates (Li et al., 2013), enzymatic activity (Bragazza et al., 2012; Li et al., 2017), or plant production (Euskirchen et al., 2009). Some other studies showed opposite results; that is, microbial respiration inhibited by warming, which resulted from decreased soil water availability (Fang et al., 2018; Liu et al., 2009), labile C (Li et al., 2019), microbial biomass C (Chen, et al., 2016), or enzymatic activity (Garcia‐Palacios et al., 2018). As a result, these contrasting responses of microbial metabolic rate to warming led to large uncertainties and contradictory predictions of climate‐C feedbacks (Bradford et al., 2010; Hartley et al., 2007, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have attempted to uncover possible mechanisms by which changes in microbial traits (biomass, physiology, community composition, etc.) or key processes such as enzyme production regulate the response of SOC to warming (e.g., Alvarez et al, 2018; Ding et al, 2016; Guo et al, 2020; Karhu et al, 2014; Li et al, 2019; Nottingham et al, 2019; Walker et al, 2018). However, the results are context dependent and vary among different ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…Acidobacteria was the most common group at low-elevation, possibly due to their low C turnover, which allows them to adapt to the low-nutrient soil environment as “stress tolerators” [ 61 ]. Of course, not all taxa in a phylum will be either copiotrophic or oligotrophic [ 60 ], hence other classifier levels should be used to predict soil C loss [ 62 ]. In our study, Beta - and Gamma - proteobacteria decreased as elevation decreased; however, Acidobacteria GP4 and GP6 increased.…”
Section: Discussionmentioning
confidence: 99%